National and Cultural Characteristics of Phraseological Units in Modern English and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper provides an in-depth analysis of how the linguistic landscape is reflected in English and Uzbek through the use of idioms. It examines the parallel existence of lexical and phraseological meanings within these expressions and explores the national and cultural specificities embedded in English and Uzbek idioms.